Individual calculation of perfusion activity based on ventilation efficiency for V/P-SPECT - Bärenfänger, Felix; Block, Andreas; Schmelz, Detlef; Hamami-Arlinghaus, Monia (Nuklearmedizin - NuclearMedicine, 2021)
Aim Implementation of the individual calculation of perfusion activity to ensure the guideline-compliant ratio of perfusion to ventilation (P/V-ratio) of ≥ 3 in the diagnosis of acute pulmonary embolism (PE) using V/P-SPECT.Material and Methods 50 consecutive V/P-SPECT examinations, in which a standard activity of 160 MBq was applied for perfusion imaging, are evaluated retrospectively. Based on this patient group an activity factor is determined, which provides a correlation between the applied perfusion activity and the expected perfusion counts of the gamma camera. Using the mean activity factor, the perfusion activity required for a P/V-ratio of four is calculated using the previously acquired ventilation count rate. This is applied prospectively to the 100 subsequent examinations.Results The mean perfusion activity factor is (54.56 ± 10.13) cps/MBq. The individually calculated perfusion activities range from 80 MBq to 200 MBq with an average value of (146.9 ± 35.3) MBq and a median of 140 MBq. The individual activity calculation thus reduced the mean perfusion activity by 8.2 % and the median by 12.5 %. In addition, the individual calculation reduced the proportion of P/V ratios < 3 from 14 % to 0 % and the proportion of P/V ratios > 5 from 24 % to 19 %.Conclusion The presented method for the individual calculation of perfusion activity offers a simple way to ensure a guideline-compliant P/V-ratio. Furthermore, unnecessarily high perfusion activity as a result of inadequate ventilation can be avoided.
Keywords: V/P-SPECT; P/V-ratio; activity factor; pulmonary embolism